2010
DOI: 10.1051/0004-6361/200913187
|View full text |Cite
|
Sign up to set email alerts
|

The XMM-NewtonWide Angle Survey (XWAS): the X-ray spectrum of type-1 AGN

Abstract: Aims. We discuss the broad band X-ray properties of one of the largest samples of X-ray selected type-1 AGN to date (487 objects in total), drawn from the XMM-Newton Wide Angle Survey (XWAS). The objects presented in this work cover 2−10 keV (rest-frame) luminosities from ∼10 42 −10 45 erg s −1 and are detected up to redshift ∼4. We constrain the overall properties of the broad band continuum, soft excess and X-ray absorption, along with their dependence on the X-ray luminosity and redshift. We discuss the imp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
63
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 71 publications
22
63
1
Order By: Relevance
“…Because the errors on the photon index are not symmetric, we used the average value for the individual errors in each case. We obtain a mean value of Γ = 2.05 ± 0.03 with an intrinsic dispersion of σ = 0.26 ± 0.02 for the BSS and Γ = 1.98 ± 0.08 with an intrinsic dispersion of σ = 0.29 ± 0.05 for the HBSS, in agreement with previous works (Mateos et al 2010;Young et al 2009;Dadina 2008;Mainieri et al 2007;Page et al 2006;Mateos et al 2005a,b). Errors were extracted from the 1σ confidence contours.…”
Section: Photon Indexsupporting
confidence: 92%
See 3 more Smart Citations
“…Because the errors on the photon index are not symmetric, we used the average value for the individual errors in each case. We obtain a mean value of Γ = 2.05 ± 0.03 with an intrinsic dispersion of σ = 0.26 ± 0.02 for the BSS and Γ = 1.98 ± 0.08 with an intrinsic dispersion of σ = 0.29 ± 0.05 for the HBSS, in agreement with previous works (Mateos et al 2010;Young et al 2009;Dadina 2008;Mainieri et al 2007;Page et al 2006;Mateos et al 2005a,b). Errors were extracted from the 1σ confidence contours.…”
Section: Photon Indexsupporting
confidence: 92%
“…We find an anti correlation between the power-law index and the X-ray luminosity (ρ = −0.21, probability = 8 × 10 −4 ) and marginally redshift (ρ = −0.10, probability = 0.09) with the Spearman rank correlation analysis. We also find a correlation with the 0.5−2 keV flux (ρ = 0.15, probability = 0.01), which could be caused by undetected intrinsic absorption as pointed out in Mateos et al (2010). In that work, the authors found a stronger correlation between the photon index and the source redshift, but in their case it mainly started above redshift 2 and our sample only contains 3 sources above that redshift.…”
Section: Photon Indexsupporting
confidence: 75%
See 2 more Smart Citations
“…The X-ray spectra are shown in Figure 2 (right panels). In the case of 2XMMJ100038.9+050955, the spectral quality does not allow us to constrain the power-law photon index and the intrinsic absorption at the same time, so we have fixed the power-law photon index Γ to 1.9, a common value for unabsorbed AGN (Mateos et al 2010, Corral et al 2011, Lanzuisi et al 2013). …”
Section: Xmm-newton Spectroscopymentioning
confidence: 99%